2012
DOI: 10.1093/ejcts/ezr242
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion of blood during cardiac surgery is associated with higher long-term mortality in low-risk patients

Abstract: Long-term follow-up of low-risk patients undergoing simple cardiac surgery demonstrates a more than 10% higher mortality when receiving perioperative RBC transfusion. Even transfusion of 1-2 units seems to carry a risk of that magnitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(50 citation statements)
references
References 24 publications
4
42
0
4
Order By: Relevance
“…However, we must take into consideration that the group using CS, 28 patients did not have UPRBC infusionn infusion, the total of 1.25 RBC / patient / hospitalization, and in Group A, 4.31. Several authors have demonstrated that the non-use RBC in the postoperative period decreases not only the morbidity but also trans and postoperative mortality [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, we must take into consideration that the group using CS, 28 patients did not have UPRBC infusionn infusion, the total of 1.25 RBC / patient / hospitalization, and in Group A, 4.31. Several authors have demonstrated that the non-use RBC in the postoperative period decreases not only the morbidity but also trans and postoperative mortality [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…The Society of Thoracic Surgeons and the Society of Cardiovascular Anesthesiologists [4], in its guidelines for 2007, considered as class I the use of CS. However, several authors have shown that the use of CS is not as beneficial as stated [5,6] and is not cost-effective [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is lifesaving after cardiac surgery, RBC transfusion increases death rates from 5.4% to 13.4% in the long term, whereas median time to death is decreased from 4.7 years to 1.1 years (3) . Even among low-risk patients undergoing simple cardiac surgery, perioperative RBC transfusion is significantly associated with mortality after more than 4500 days (5) . In the short term, RBC transfusion ≥4 units is an independent predictor of one-year mortality (2) .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Despite being a common and widespread practice, the use of blood products is associated with an increased risk of infections, renal dysfunction and mortality, as already demonstrated. [4][5][6][7] In addition, normal hemoglobin levels are not necessarily related to better outcomes postoperatively, and in some cases, may be advantageous to tolerate lower HB levels, avoiding unnecessary blood transfusions. 8 Safety of blood transfusion can be defined as a series of processes implemented to eliminate or reduce inherent risks of transfusions.…”
Section: Introductionmentioning
confidence: 99%